Skill Building Sequence for Choral Ensembles: Teacher’s Guide for Children’s Choir - Miceli, Jennifer (Hamilton Books, 2015)
The ability to bring meaning to music notation without the assistance of an accompanist playing choral parts is a requisite skill on a musician’s journey to self-reliance and full artistic expression. Despite its importance, high performance expectations pose a challenge for choir directors to allocate discrete rehearsal time to music reading skill development. Consider for a moment an embedded music reading system that facilitates choristers’ ability to read their choral octavos; a process that develops rhythm and tonal musicianship and gives choristers the tools they need to learn music on their own. This bookintroduces an adaptable, literature-based choral music reading approach that empowers young singers with music literacy skills that point beyond the choral rehearsal and encourage independent and group music making for a lifetime.